2017
DOI: 10.1371/journal.pgen.1007006
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication stress restricts ribosomal DNA copy number

Abstract: Ribosomal RNAs (rRNAs) in budding yeast are encoded by ~100–200 repeats of a 9.1kb sequence arranged in tandem on chromosome XII, the ribosomal DNA (rDNA) locus. Copy number of rDNA repeat units in eukaryotic cells is maintained far in excess of the requirement for ribosome biogenesis. Despite the importance of the repeats for both ribosomal and non-ribosomal functions, it is currently not known how “normal” copy number is determined or maintained. To identify essential genes involved in the maintenance of rDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 51 publications
4
85
1
Order By: Relevance
“…While Chr XII-specific destabilization under reduced-initiation conditions has been observed previously (Ide et al, 2007; Salim et al, 2017; Sanchez et al, 2017), our observations of rDNA array instability suggest a slightly different interpretation of a similar phenomenon described by Ide et al (Ide et al, 2007). After shifting asynchronously-growing orc1-4 cells to the non-permissive temperature, Ide et al (2007) reported that instability of Chr XII preceded instability of the other chromosomes.…”
Section: Discussioncontrasting
confidence: 55%
“…While Chr XII-specific destabilization under reduced-initiation conditions has been observed previously (Ide et al, 2007; Salim et al, 2017; Sanchez et al, 2017), our observations of rDNA array instability suggest a slightly different interpretation of a similar phenomenon described by Ide et al (Ide et al, 2007). After shifting asynchronously-growing orc1-4 cells to the non-permissive temperature, Ide et al (2007) reported that instability of Chr XII preceded instability of the other chromosomes.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, reducing rDNA copy number was neither necessary nor sufficient to explain SIR -mediated suppression of cdc6-4 . Cells harboring a reduction in rDNA copy number in cdc6-4 sir2Δ populations likely arise because loss of Sir2 increases recombination frequency within the rDNA array, and rDNA copy numbers are reduced over time in many mutants compromised for replication initiation [35,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Copy number is a rapidly evolving trait, and mechanisms for both rDNA copy number expansion and contraction have been described (Szostak & Wu, ). The consequences of rDNA CNV have received considerable attention in the context of DNA damage response (Ide, Miyazaki, Maki, & Kobayashi, ), DNA replication stress (Salim et al, ) and the expression of nonribosomal genes (Paredes, Branco, Hartl, Maggert, & Lemos, ). Similarly, the ecological importance of rDNA CNV has also been well characterized, with rDNA copy number being linked to ecosystem stoichiometry (Elser et al, ), growth rate and competitive ability (Klappenbach, Dunbar, & Schmidt, ; Nemergut et al, ) as well as bias in estimates of organismal abundance in high‐throughput amplicon sequencing (Kembel et al, , Perisin, Vetter, Gilbert, & Bergelson, ).…”
Section: Introductionmentioning
confidence: 99%